A review on the digitalization of integrated halal assurance and quality management system - Puspaningtyas, Shinta Diah; Hidayati, Luki; Ni'maturrakhmat, Viko Nurluthfiyadi (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2026)
Complex global food chains and rising demand for high-quality halal product requires better and more efficient management. Traditionally, the Halal Assurance System (HAS) and Quality Management System (QMS) have been implemented separately, resulting in overlapping processes and redundant documentation. In the era of digital transformation and Industry 4.0, integrating these systems digitally improves traceability, compliance, and overall organization’s performance. This review aimed to examine current trends, technologies, and research gaps related to the digitalization of integrated Halal and Quality Management Systems (HAS–QMS). A comprehensive literature analysis highlights the role of emerging technologies—such as blockchain, the Internet of Things (IoT), artificial intelligence (AI), cloud computing, and big data analytics—in supporting halal integrity and quality assurance across the food value chain. The findings indicated that digital integration facilitates real-time monitoring, automated documentation, and improved audit readiness. However, challenges persist in areas such as data interoperability, standard harmonization, regulatory acceptance, and the digital readiness of small and medium enterprises. The paper proposed a conceptual framework for the digitalized integration of HAS and QMS, aligning technological capabilities with halal and quality compliance requirements. To align with industry 5.0, future research should standardize models, test performance, and integrate sustainability and ethical standards.